2012
DOI: 10.1007/s13238-012-2097-3
|View full text |Cite
|
Sign up to set email alerts
|

Intersection of autophagy with pathways of antigen presentation

Abstract: Traditionally, macroautophagy (autophagy) is viewed as a pathway of cell survival. Autophagy ensures the elimination of damaged or unwanted cytosolic components and provides a source of cellular nutrients during periods of stress. Interestingly, autophagy can also directly intersect with, and impact, other major pathways of cellular function. Here, we will review the contribution of autophagy to pathways of antigen presentation. The autophagy machinery acts to modulate both MHCI and MHCII antigen presentation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 69 publications
1
19
0
Order By: Relevance
“…Autophagy is a host-defense mechanism against mycobacterial infection (55,56) that enhances peptide presentation by DCs (57). In the current study, we have also found that annexin1 regulates autophagy in DCs and that autophagy can serve as an effective system for the delivery of exogenous antigens in cross-presentation (58,59). Furthermore, it has been shown that following efferocytosis, autophagy promotes apoptotic cell degradation (60).…”
Section: Discussionsupporting
confidence: 54%
“…Autophagy is a host-defense mechanism against mycobacterial infection (55,56) that enhances peptide presentation by DCs (57). In the current study, we have also found that annexin1 regulates autophagy in DCs and that autophagy can serve as an effective system for the delivery of exogenous antigens in cross-presentation (58,59). Furthermore, it has been shown that following efferocytosis, autophagy promotes apoptotic cell degradation (60).…”
Section: Discussionsupporting
confidence: 54%
“…Peptides or unfolded proteins can bind to MHCII at the cell surface where they are directly displayed for T cell recognition 27 . Similarly autophagocytosis can deliver cytosolic proteins to endosomal compartments for MHCII antigen presentation 28 . Exosome transfer of MHCII molecules, and their cargoes further diversifies the potential conditions for antigen presentation 29 .…”
Section: General Mechanisms Of Antigen Presentation By Mhcii Moleculesmentioning
confidence: 99%
“…Moreover, it is essential for the survival and function of B1 cells and plasma cells [ 20 ]. ( 5 ) As is illustrated here, autophagy participates in MHCII antigen presentation, and it could impact MHCI presentation as well [ 21 ]. APCs, antigen-presenting cells; CMA, chaperone-mediated autophagy; LAMP-2A, lysosomal-associated membrane protein type 2A; MAP1LC3/LC3, microtubule associated protein 1 light chain 3; ly-HSPA8 and ly-HSP90, lysosomal luminal HSPA8 and HSP90; MIIC, late endosomal MHC class II compartment; MHCI and II, major histocompatibility complex class I and II; IL-6 and -8, interleukin-6 and -8; PM, plasma membrane; TCR, T-cell receptor; TLR, toll-like receptor.…”
Section: Figurementioning
confidence: 99%